2016
DOI: 10.18632/oncotarget.14122
|View full text |Cite
|
Sign up to set email alerts
|

Genomic differences between black and white patients implicate a distinct immune response to papillary renal cell carcinoma

Abstract: Significant disparities in survival, incidence and possibly response to current therapies exist between black and white patients with renal cell carcinoma (RCC). Recent genomic evidence to account for these disparities has been reported for clear cell RCC. However, racial disparities at the genomic level for papillary RCC (pRCC) which is a genetically distinct and less responsive histologic subtype of RCC have not been reported. Using The Cancer Genome Atlas (TCGA) data, the present study assessed gene-level e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Human genetics contribute to the propensity and severity of diseases 21,[30][31][32][33][34][35][36][37] . Sometimes the contribution is straightforward; a single allele variation found in Ashkenazi Jews, causes the vast majority of Tay-Sachs disease 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Human genetics contribute to the propensity and severity of diseases 21,[30][31][32][33][34][35][36][37] . Sometimes the contribution is straightforward; a single allele variation found in Ashkenazi Jews, causes the vast majority of Tay-Sachs disease 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this gene has successfully been used as a classifier to distinguish between racial groups. Further, higher CRYβB2 expression has been correlated to poorer outcome in cancer, regardless of race [7, 11, 12, 1416]. Even with these findings, no study has demonstrated a functional role for CRYβB2 in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…15 Paulucci et al demonstrated different immune responses to cancer between black and white patients. 16 Thus, there exists the possibility that genomic or molecular differences between NHB and NHW patients might cause distinct survival outcomes. This conclusion can inspire further explorations.…”
mentioning
confidence: 99%